GOLPH3 induces epithelial–mesenchymal transition via Wnt/β‐catenin signaling pathway in epithelial ovarian cancer. (23rd March 2017) - Sun, Jing; Yang, Xiaoming; Zhang, Ru; Liu, Suqing; Gan, Xupei; Xi, Xiaowei; Zhang, Zhenbo; Feng, Youji; Sun, Yunyan
Abstract: Golgi phosphoprotein 3 ( GOLPH3 ), a newly recognized oncogene, is associated with tumor growth, metastasis, and poor prognosis in several types of cancer. However, its biological role and underlying mechanism in epithelial ovarian cancer (EOC) remain poorly understood. Here, we found that GOLPH3 was overexpressed in EOC tissues and cell lines. This overexpression promoted the migration and invasion of EOC cells. Moreover, GOLPH3 upregulated the expression of epithelial–mesenchymal transition (EMT) markers, such as N‐cadherin and Snail, and the Wnt/ β ‐catenin‐related genes cyclin‐D1 and c‐Myc, which were restored via silencing of GOLPH3 expression. Furthermore, the inhibitor and activator of the Wnt/ β ‐catenin pathway, XAV939 and LiCl, enhanced or decreased, respectively, the effect of GOLPH3 on EMT, which further confirmed that GOLPH3 promoted EMT progression via activation of Wnt/ β ‐catenin signaling. In addition, we found that EDD, the human hyperplastic discs gene, was consistent with GOLPH3 expression and also promoted the EMT process and activated Wnt/ β ‐catenin signaling. These findings demonstrate that EDD might be a downstream factor of GOLPH3 . Taken together, our findings demonstrate the existence of a GOLPH3–Wnt/ β ‐catenin–EMT axis in EOC and provide a new therapeutic target to treat EOC. Abstract : We treated three different cell lines to confirm that GOLPH3 promoted EMT process and metastasis in epithelial ovarian cancer. Furthermore, we successfully proved the existence of GOLPH3–Wnt/ β ‐catenin–EMT axis in epithelial ovarian cancer.